Evaluating the level of training in improving professional performance from the point of view of medical and paramedical personnel. A field study on Ibn Sina Teaching Hospital in Sirte (Economic studies journal, 2021)
AbstractThe study aimed to the evaluation of training to improve the performance from the viewpoint of the assistant medical staff in Ibis Sine Teaching Hospital in Sirte.The study problem focused on the following main question:What is the level of training in Ibis Sine Teaching Hospital in Sirte from the viewpoint of the assistant medical? Staff?The study relied on the descriptive approach to achieve its objectives, using a questionnaire form, prepared as a toolTo collect the study data, distributed to the intentional sample (200) recovered (174) all of them are valid for the Study, representing (23.26%) from (748) assistant medical staff, and analyzed the data of the study and test Hypotheses, through the implementation of the programs of (SPSS and Minitab)The most important results of the study:• Feeling of staff (study sample) decrease of training level in Ibis Sine Teaching Hospital in Sirte, through the Difference dimensions (type and the period of training)أبريل 2021• There is statistically significant relationship at the level of significance (0.05) between the type of training and The performance improvement of assistant medical staff.• There is statistically significant relationship at the level of significance (0.05) between the periods of training And the performance improvement of assistant medical staff.
Keywords: Evaluation; Training; Performance; Assistant medical staff; Type of training -period of training